Pengembangan Sumber Daya Aparatur di Pemerintah Kota Kupang Melalui Pendidikan dan Pelatihan Berbasis Kompetensi - Christo Vorando Amalo (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2018)
In order to support good governance, it is necessary to develop civil servants, one of the ways is through competency-based education and training. But the fact is that civil servants who are included in the training are not in accordance with competencies that are influenced by various factors. The purpose of this study was to find out how the competency development of civil servants in Kupang City Government and to collect the necessary data and information related to factors that influence the development of competencies of civil servants in Kupang City Government. The sampling technique is done by purposive sampling. The location of the study was carried out on the Regional Apparatus of the Kupang City Government. The research method uses is a qualitative approach and the type of this research is a case study. The results of the study showed that the development of Civil Servants competencies varied depending on the characteristics of post-training Civil Servants, leadership style, and work climate. This is caused by local political factors, like and dislike, collusion and nepotism, hopes for civil servants after training and fair treatment.